A new dimension. - Fuyuno, Ichiko (Far Eastern Economic Review, 2001)
In June 2001, J-Phone, the third largest mobile phone company in Japan, will launch the world's first handset to display 3-D images on screen. Three-D images are exactly the sort of content that has made wireless Internet-enabled phones such a success in Japan, and this innovation reveals how new capabilities are making cellphones more powerful. The J-SH07 handset produced by J-Phone is fitted with Sun Microsystems' Java programming language, and this allows users to download games, animation, music, and other software from the Internet. However, insiders feel that demand for 3-D content is not growing as quickly as expected, because creating 3-D images is complex and costly. Despite this, J-Phone regards the product as the natural step forward toward applying 3-D technology to the budding industry of mobile commerce. {p